A red seaweed Kappaphycus alvarezii-based biostimulant (AgroGain®) improves the growth of Zea mays and impacts agricultural sustainability by beneficially priming rhizosphere soil microbial community - Nivetha, Nagarajan; Shukla, Pushp Sheel; Nori, Sri Sailaja; Kumar, Sawan; Suryanarayan, Shrikumar (Frontiers in Microbiology, 2024)
The overuse of chemical-based agricultural inputs has led to the degradation of soil with associated adverse effects on soil attributes and microbial population. This scenario leads to poor soil health and is reportedly on the rise globally. Additionally, chemical fertilizers pose serious risks to the ecosystem and human health. In this study, foliar sprays of biostimulant (AgroGain/ LBS6) prepared from the cultivated, tropical red seaweed Kappaphycus alvarezii increased the phenotypic growth of Zea mays in terms of greater leaf area, total plant height and shoot fresh and dry weights. In addition, LBS6 improved the accumulation of chlorophyll a and b, total carotenoids, total soluble sugars, amino acids, flavonoids, and phenolics in the treated plants. LBS6 applications also improved the total bacterial and fungal count in rhizospheric soil. The V3-V4 region of 16S rRNA gene from the soil metagenome was analysed to study the abundance of bacterial communities increased in the rhizosphere of LBS6-treated plants. Treatments were found to enrich beneficial soil bacteria, i.e., Proteobacteria especially the class Alphaproteobacteria, Cyanobacteria, Firmicutes, Actinobacteriota, Verrucomicrobiota, Chloroflexi, Acidobacteriota and several other phyla related to plant growth promotion. A metagenomic study of those soil samples from LBS6 sprayed plants was correlated with functional potential of soil microbiota. Enrichment of metabolisms such as nitrogen, sulphur, phosphorous, plant defense, amino acid, co-factors and vitamins were observed in soils grown with LBS6 sprayed plants. These results were further confirmed by the significant increase in the activity of soil enzymes such as urease, acid phosphatase, FDAse, dehydrogenase, catalase, and biological index of fertility in the rhizosphere of LBS6-treated corn plant. These findings conclude that the foliar application of LBS6 on Z. mays improve and recruit beneficial microbes and alter soil ecology in a sustainable manner.